2012
DOI: 10.1515/epoly.2012.12.1.227
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on the effects of galbanic acid, galbanic ferric salt and tetrabromo galbanic acid on photo-oxidative degradation of linear low density (LLDPE) films

Abstract: Galbanic acid (GA) is known as an effective photo-sensitizing agent in polyethylene. This paper reports the comparative studies on photo-oxidative degradation of LLDPE films in the presence of varying amounts of galbanic ferric salt (Fe-GA), tetrabromo galbanic acid (Br-GA), GA at the optimum concentration of 0.2% (w/w) and the pure polymer film, exposed to Ultra-Vitalux sun lamp. The degradation rate was monitored through the changes in mechanical properties (retained elongation at break and retained tensile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Also, GA was known as an effective photosensitizing agent in polyethylene. Shahmir and Assempour (2012) studied photo-oxidative degradation of LLDPE films in the presence of varying amounts of GA ferric salt (Fe-GA). Results showed that the photo-activity of GA in the polymer arises from the C¼C bond presents in the side group attached to aromatic lactone rings of additive molecule.…”
Section: Total Synthesis Of Gamentioning
confidence: 99%
“…Also, GA was known as an effective photosensitizing agent in polyethylene. Shahmir and Assempour (2012) studied photo-oxidative degradation of LLDPE films in the presence of varying amounts of GA ferric salt (Fe-GA). Results showed that the photo-activity of GA in the polymer arises from the C¼C bond presents in the side group attached to aromatic lactone rings of additive molecule.…”
Section: Total Synthesis Of Gamentioning
confidence: 99%